(untitled) (PETITUM, 2021)
ABSTRACT: Education Implementation is the activity of managing the components of the education system in secondary education and special education units so that the education process can take place in accordance with national education goals. Thus, in order to carry out government affairs in the field of education, which is a mandatory matter for the Province according to the scope of its authority and responsibility, it is necessary to regulate the aspect of autonomy to provide legal certainty in the implementation of education that is integrated and comprehensive so that it can encourage the creation of competitive, democratic and human resources. responsibility based on local wisdom. Through the socialization of "Regional Regulation Number 2 of 2016 concerning the Implementation of Education", it is hoped that it will be able to increase understanding of the implementation of education in the province of South Sulawesi. There are problems facing the world of education, especially higher education in Indonesia, which are indicated by low equality in obtaining education, weak education management, and low quality and relevance of education. Thus, to realize the goals and strategies in organizing and/or managing education, regulations are needed to fulfill the basic rights and obligations of community members in the field of education. ABSTRAK: Penyelenggaraan Pendidikan adalah kegiatan pengelolaan komponen sistem pendidikan pada satuan pendidikan menengah dan pendidikan khusus agar proses pendidikan dapat berlangsung sesuai dengan tujuan pendidikan nasional. Dengan demikian, untuk menyelenggarakan urusan pemerintahan bidangpendidikan yang merupakan urusan wajib oleh Provinsi sesuai lingkup kewenangan dan tanggung jawabnya, maka perlu pengaturan dari aspek otonomi untuk memberikan kepastian hukum dalam penyelenggaraan pendidikan yang bersifat terpadu dan komprehensif sehingga dapat mendorong terciptanya sumberdaya manusia berdaya saing, demokratis dan bertanggung jawab yang berbasis kearifan lokal. Melalui sosialisasi “Peraturan Daerah Nomor 2 Tahun 2016 tentang Penyelenggaraan Pendidikan”, diharapkan mampu meningkatkan pemahaman penyelenggaraan pendidikan di provinsi sulawesi selatan. Adapun problematika yang dihadapi dunia pendidikan khususnya pendidikan tinggi di Indonesia, yang diindikasikan dengan rendahnya pemerataan dalam memperoleh pendidikan, lemahnya manajemen pendidikan, serta rendahnya kualitas dan relevansi pendidikan. Dengan demikian untuk mewujudkan tujuan dan strategi dalam penyelenggaraan dan/atau pengelolaan pendidikan, diperlukan pengaturan agar terpenuhi hak-hak dan kewajiban yang mendasar bagi warga masyarakat di bidang pendidikan.